Radiochemotherapy and Immunotherapy for A Tracheal Carcinoma - Larnaudie, A.; Orliac, H.; Deny, N.; Naessens, C.; Serre, R.; Clavere, P. (Archives of Clinical and Medical Case Reports, 2022)
Tracheal cancer is a rare localization with a lack of treatment consensus. A 45-year-old man presented a tracheal squamous cell carcinoma with mediastinal nodes and oesophagus involvement. Treatment consisted in induction chemotherapy, radiochemotherapy and immunotherapy. The different PET realised before, during and after induction chemotherapy helped to precise the radiotherapy volumes. Three months after radiochemotherapy, PET CT showed a partial response. We report choices done in our service in terms of radiotherapy and systemic treatment.